Kepemimpinan Moral Spiritual untuk Karakter Religius di MTs Nurul Hidayah Pemalang - Imam Ghazali; Sitti Hartinah DS; Dewi Apriani (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2025)
The moral and spiritual leadership model plays a strategic role in shaping the religious character of students at MTs Nurul Hidayah Majalangu, Watukumpul, Pemalang. Initial conditions indicate weak implementation of religious programs and low student awareness of worship practices, reflecting the suboptimal effectiveness of the conventional leadership style still in use. Through a qualitative approach based on literature review, it was found that values such as role modeling, responsibility, honesty, and the integration of religious values into policies and learning processes can have a positive impact on students' religious character. The success of this model is strongly influenced by the active involvement of teachers, parental participation, community support, as well as continuous supervision and evaluation. The systematic and collaborative application of moral and spiritual leadership is recommended as an effective strategy for strengthening religious character education in the madrasah environment. Keywords: Moral leadership, spiritual leadership, religious character, madrasah education, role modeling, religious values, literature review.